The Influence of Strategic Digital Leadership and Organizational Communication in Improving Organizational Performance in Educational Institutions - Sarfilianty Anggiani; Feti Fatonah (Journal of Social Research, 2024)
This study aims to analyze the influence of strategic digital leadership and organizational communication in improving organizational performance in Educational Institutions. This is because since the Covid-19 outbreak, several Educational Institutions have not been able to survive and eventually closed. The Covid-19 Pandemic has so far changed many things, especially changing various aspects of human life today, especially in the world of education. This situation requires all elements of education to adapt. Therefore, the role of a leader in an Educational Institution is very important in determining the right strategy, in order to maintain the Educational Institution he leads. The data sources used in this study are primary data sources. The primary data referred to in this study are questionnaires distributed to respondents. Data collection is cross-sectional or one shot using questionnaires distributed online. Structural Equation Modeling (SEM) PLS version 3 is used for data analysis. The results of the study showed that there is a positive influence of organizational communication on organizational performance. This indicates that with effective communication owned by an Educational Institution, it can improve organizational performance. Considering that communication is an important indicator in improving the performance of an organization. The better and more effective the communication that takes place in the organization, the healthier and more open the work climate will be, which will increase productivity. There is a positive influence of strategic digital leadership on organizational performance. This indicates that by implementing strategic digital leadership properly and effectively, it can improve the performance of the organization.